Discursive Properties as Argumentative Strategy in Enem Essays - Sá, Kleiane Bezerra de (Linha D’Água, 2023)
In the following article, our extensive objective is to propose a reflection on the relationship between the discursive topic and the argumentation provided by candidates in Exame Nacional do Ensino Médio (ENEM) essays. Our starting point is the redefinition of the characterizing traits of topic properties, namely centering and organicity, to explore argumentative development by the means of defining the most relevant subtopics to the defense of one’s point of view in dissertation-argumentative texts. Therefore, we analyze, based on the conclusions of our doctoral thesis, how hierarchization of information ensues in regard to the broadening and deepening of subtopics in a maximum grade essay of Enem 2022, all considering the elaboration of a discursive topic table. We believe that the reflections engendered by this article can subsidize teaching work, insofar as the exercise of analyzing the topic organization benefits Enem candidates by developing their ability to organize ideas.